Global Deletion of the Prolactin Receptor Aggravates Streptozotocin-Induced Diabetes in Mice - Ramirez-Hernandez, Gabriela; Adan-Castro, Elva; Diaz-Lezama, Nundehui; Ruiz-Herrera, Xarubet; Martinez de la Escalera, Gonzalo; Macotela, Yazmin; Clapp, Carmen (Frontiers in Endocrinology, 2021)
Prolactin (PRL) levels are reduced in the circulation of rats with diabetes or obesity, and lower circulating levels of PRL correlate with increased prevalence of diabetes and a higher risk of metabolic alterations in the clinic. Furthermore, PRL stimulates β-cell proliferation, survival, and insulin production and pregnant mice lacking PRL receptors in β-cells develop gestational diabetes. To investigate the protective effect of endogenous PRL against diabetes outside pregnancy, we compared the number of cases and severity of streptozotocin (STZ)-induced hyperglycemia between C57BL/6 mice null for the PRL receptor gene (Prlr-/-) and wild-type mice (Prlr+/+). STZ-treated diabetic Prlr-/- mice showed a higher number of cases and later recovery from hyperglycemia, exacerbated glucose levels, and glucose intolerance compared to the Prlr+/+ mice counterparts. Consistent with the worsening of hyperglycemia, pancreatic islet density, β-cell number, proliferation, and survival, as well as circulating insulin levels, were reduced, whereas a-cell number and pancreatic inflammation were increased in the absence of PRL signaling. Deletion of the PRL receptor did not alter the metabolic parameters in vehicle-treated animals. We conclude that PRL protects whole body glucose homeostasis by reducing β-cell loss and pancreatic inflammation in STZ-induced diabetes. Medications elevating PRL circulating levels may prove to be beneficial in diabetes.